Concepciones religiosas del más allá en la Edad del Hierro de la Península de Omán: una visión aproximativa desde las arenas del Rub Al-Khali - Mañé Rodríguez, M. (ISIMU, 2016)
Rub’al-Khali is one of the largest and most arid deserts on the planet. The extreme conditions experienced in that region have had a strong influence on the existence of man since ancient times. The Iron Age peoples in the Oman Peninsula were no exception. This article centres mainly on the search for evidence of their religious beliefs with respect to the afterlife, based not only on the archaeological finds in this area, but also on those from the opposite extreme of the desert, which seems to reflect a similar way of life, and on the ethnographical observations carried out in the Oman Peninsula before the oil boom.